PERLINDUNGAN HAK REPRODUKSI ISTRI ATAS PEMBATASAN KEMAMPUAN SUAMI YANG DIKENAI PIDANA KEBIRI KIMIA: KAJIAN HUKUM KELUARGA DAN HAM - Yelmi Wahyuni Nafalia; Harris Retno Susmiyati; Rini Apriyani (Jurnal Ilmiah Advokasi, 2026)
This study aims to examine two main issues: first, whether the imposition of chemical castration as a criminal sanction is consistent with the objectives and principles of sentencing in Indonesia; and second, how the right of a spouse to have offspring is protected when the husband is subjected to chemical castration, from a human rights perspective. This research employs a doctrinal legal approach, using primary legal materials including the Indonesian Penal Code, Law No. 39 of 1999 on Human Rights, and Law No. 17 of 2016 concerning amendments to child protection regulations. The right to have offspring is understood as part of fundamental human rights related to family life, reproductive autonomy, and human dignity, as recognized under national law and international human rights instruments, including the International Covenant on Civil and Political Rights (ICCPR) and the International Covenant on Economic, Social and Cultural Rights (ICESCR). This study finds that chemical castration, although intended to deter sexual offenses, raises significant human rights concerns. These concerns do not solely arise from the issue of permanent infertility, but rather from the restriction of the biological functions of the convicted individual, the limitation of the spouse’s reproductive rights within marriage, and the potential violation of the principle of human dignity. Furthermore, from a normative legal perspective, the policy raises questions regarding its compatibility with the goals of sentencing, particularly in relation to proportionality and respect for fundamental rights. Accordingly, the protection of the spouse’s right to have offspring must be ensured through a human rights-based approach, both within national legal frameworks and international legal standards, emphasizing the need for a more balanced and rights-respecting criminal policy. Keywords: Chemical Castration, Human Rights, Reproductive Rights, Legal Protection